Anisotropic isoperimetric inequalities involving boundary momentum, perimeter and volume. (October 2019) - Paoli, Gloria; Trani, Leonardo
Abstract: We consider a scale invariant functional involving the anisotropic p -momentum, the anisotropic perimeter and the volume. We show that the Wulff shape, associated with the Finsler norm F considered and centered at the origin, is the unique minimizer of the anisotropic functional taken into consideration among all bounded convex sets. Highlights: A particular anisotropic and scale invariant functional is considered. The functional is minimized among all convex and bounded sets. The Wulff shape is the unique minimizer of this anisotropic functional.